In Search of Conceptual Platforms for East-West Cooperation, Global and Regional Integration Projects - Valentin Yakushik (Философия и космология, 2021)
This article seeks to reflect on some theoretical and practical issues raised at the Conference “Common Foreign and Security Policy of European Union. Middle East and Iran,” organized by Allameh Tabataba’i University, with the support of the Erasmus+ Programme of the European Union (EU Education, Audiovisual and Culture Executive Agency – EACEA). The conference took place in Tehran, Iran, on 21 December 2020. The paper looks into aspects of the conceptual platforms for EastWest cooperation, global and regional integration projects, and is intended as an appeal for intensifying pluralistic joint academic research, culturally and politically unbiased, to theoretically generalize, compare and make available to a wider public the experience of the EU and other institutionalized regional communities, in order to foresee the possible and most viable forms of coordination of strategic (and tactical) policies within the developing regionalization processes. The main proposed methods of academic research are typologization, comparative and contrasting analysis, extrapolation.